Application of hypoxicators in the rowers` training - Neykov, S.; Bachev, V.; Petrov, L.; Alexandrova, A.; Andronov, A.; Kolimechkov, A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Purpose: Intermittent altitude exposure leads to improvements in aerobic performance and blood parameters of athletes. The variety of hypoxic devices and simulated altitude training models requires a detailed study of their effects to achieve the best results. The aim of this study was to investigate the effect of a four-week training camp at sea level conditions, combined with normobaric hypoxia, provided by hypoxicators during the night`s sleep of the athletes. Material: Sixteen rowers of the Bulgarian national team (17.13±0.83 years old) were divided into a control group (n=8) and an experimental group (n=8) subjected to hypoxia for a period of four weeks. At the beginning and end of the training camp, anthropometric and hematological data were measured. A submaximal test on the Concept II rowing ergometer was performed, and the physical work capacity and anaerobic threshold were determined. Results: The results showed: 1) a lack of significant changes in the aerobic performance after training camp, both within and between groups; 2) at the end of the training camp in the experimental group a statistically significant increase in hemoglobin concentration (156.25±4.11 vs 162.75±4.11 g/L, p<0.01) and erythrocyte count (5.26±0.13 vs 5.49±0.10 g/L, p<0.01) was observed. Conclusions: The encouraging results regarding the higher increase in blood oxygen-carrying capacity in the experimental group did not lead to an increased working capacity. Further research should be provided in the search for optimal hypoxic training parameters, allowing not only a rise in hemoglobin concentration, but also the preservation of blood rheological properties